2017
DOI: 10.1002/jso.24789
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of tumor length in patients receiving esophagectomy for esophageal cancer

Abstract: Tumor lengths on pathology were found to be the most predictive of patient outcome. However, after accounting for other tumor-related factors, tumor length only resulted in a marginal improvement in predictive accuracy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 35 publications
1
12
0
Order By: Relevance
“…The view that tumor size has a negative effect on predicting survival is supported by many investigators; however, the relationship between the T stage and discriminatory value of tumor size is still underappreciated [20][21][22][23]. Our study identified tumor size as an independent prognostic factor in T1-2 stage esophageal cancer patients, which is in line with previous results [12,13].…”
Section: Discussionsupporting
confidence: 90%
“…The view that tumor size has a negative effect on predicting survival is supported by many investigators; however, the relationship between the T stage and discriminatory value of tumor size is still underappreciated [20][21][22][23]. Our study identified tumor size as an independent prognostic factor in T1-2 stage esophageal cancer patients, which is in line with previous results [12,13].…”
Section: Discussionsupporting
confidence: 90%
“…Patients with inoperable disease undergoing ‘open and close’ procedures, with no resection, were excluded. The data set included demographic, treatment and pathology details along with complications. The study was approved by the Queen Elizabeth Hospital clinical audit department.…”
Section: Methodsmentioning
confidence: 99%
“…As the three most important predictors, T (primary tumor), N (lymph node), and M (metastasis) are the cornerstones of the current stage classification in esophageal squamous cell carcinoma (ESCC) (2). In addition, several other characteristics have also been reported as independent predictors, including tumor location, histology, differentiation, and circumferential resection margin (9)(10)(11)(12). Whether lymphovascular invasion (LVI) in ESCC should be recognized as an independent prognostic factor for survival is a controversial issue in clinical research (13).…”
Section: Introductionmentioning
confidence: 99%